Correlates of job performance and job satisfaction of nurse corps officers in selected military hospitals - De Vera, Ricardo P.
Continuous quality improvement of patient care is great challenge to all nurses throughout the world. It is not only the responsibility of the nurse administrators but also of the individual nurse to monitor the sustainment or improvement of the quality of patient care, but also of the individual nurse as well. Thus, monitoring of the performance and satisfaction through appraisal, counselling, and quality control activities are done to improve and maintain nursing care delivered to the clientele.This study aims to determine the relationship among selected antecedent variables to job performance and job satisfaction. Specially, the intention is to evaluate the levels of job performance and job satisfaction of military nurses, and their correlates. Assessment of job satisfaction and job performance is found to be effective in the maintenance or improvement of nursing care delivery.The conceptual framework of the study is established on the fact that independent variables, such as socio-demographic factors and work related factors may affect the performance and satisfaction of military nurses. Considered for the socio-demographic factors: age, sex, and civil status, while for the work related factors included are: position, educational attainment, salary, rank, and length of service. Corollary, on relationship between job satisfaction and job performance is considered. Descriptive correlational survey method was used in this study which was conducted in four military hospitals of the major services found in Metro Manila from June to December 199. With 77 military nurses participating in the study, the following are the findings:1. On the relationship between personality traits and performance.Personality traits that are dominant in good performing nurses are: emotionally stable, cooperative, practical, organized, imaginative, and forgiving. Traits of moderate performing nurses are: cooperative, relaxed serious, trusting, careful, sensitive, and responsible. Finally, the dominant traits of low performing nurses are: trusting and conscientious.2. On the relationship between socio-demographic factors and job performance/job satisfaction.Socio demographic variables are said to be correlated with performance and satisfaction of military nurses. Performance and age are strongly correlated, while civil status has negative moderate correlation. Sex is moderately correlated with performance.With respect to satisfaction, sex has negative strong correlation, while the age and civil status have a negative moderate correlation.3. On relationship between work related factors and nurses' job performance/satisfaction.